Mission on the margins: A proposal for an alternative missional paradigm in the wake of COVID-19 - Mpofu, Buhle (HTS teologiese studies, 2020)
This article proposes a critical paradigm to identify missional areas that have received scant attention from the church and to theorise ways in which alternative modes of doing mission in the context of coronavirus disease 2019 (COVID-19) present a solution against tendencies which marginalise and exploit the poor. Examining ways in which local churches in South Africa responded to challenges posed by COVID-19, the article identifies socioeconomic challenges that have been neglected by the church to posit that COVID-19 has disrupted traditional practices and exposed missional blind spots. Building on Keum’s ideas of ‘reversal of roles’ and a shift of the mission concept from ‘mission to the margins’ to ‘mission from the margins’, the article notes that shifting of religion from public to private sphere as a result of COVID-19 will redefine the church and proposes that church mission should be located where the poor people are. The article concludes that COVID-19 disruptions allow for emergence of alternative ways of being church and new modes of socioeconomic organisation with new possibilities presented through an alternative theoretical hermeneutics of missiology that locates experiences of the poor at the centre.Contribution: This article represents a systematic and practical reflection within a paradigm in which the intersection of philosophy, religious studies, social sciences, humanities and natural sciences generate an interdisciplinary, multidisciplinary and transdisciplinary contested discourse.